2012
DOI: 10.1039/c2dt30659j
|View full text |Cite
|
Sign up to set email alerts
|

A new, higher yielding synthetic route towards dodecaphenyl cage silsesquioxanes: synthesis and mechanistic insights

Abstract: Cage dodecaphenylsilsesquioxane (T12-Phenyl) was synthesized in a one batch, mildly basic aqueous solution under room temperature conditions using a trialkoxysilane precursor. Significant improvements in synthetic yield (>95%) were observed compared with previous reports. Kinetic studies of the hydrolysis of phenyltrimethoxysilane were conducted and the condensation was monitored by (29)Si NMR which revealed the presence of a transient, intermediary T1 species as the pathway to dodecaphenylsilsesquioxane spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…The method was used in the study of alterations in the composition of primary intermediates in the hydrolysis–condensation reaction of phenyltrichlorosilane leading to (tetrahydroxy)(tetraphenyl)cyclotetrasiloxane, [PhSi(HO)O] 4 [16]. The 29 Si NMR spectroscopy method demonstrated that the reaction of hydrolysis–condensation of phenyltrimethoxysilane in the presence of a basic catalyst in different conditions occurred through an intermediate, tetrahydroxy(diphenyl)disiloxane [17]. When the reaction mixture was diluted, dodecaphenyldodecasilsesquioxane (phenyl-T 12 ) was obtained in 95% yield, while an increase in the concentration of the starting compound led to PPhSSO [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was used in the study of alterations in the composition of primary intermediates in the hydrolysis–condensation reaction of phenyltrichlorosilane leading to (tetrahydroxy)(tetraphenyl)cyclotetrasiloxane, [PhSi(HO)O] 4 [16]. The 29 Si NMR spectroscopy method demonstrated that the reaction of hydrolysis–condensation of phenyltrimethoxysilane in the presence of a basic catalyst in different conditions occurred through an intermediate, tetrahydroxy(diphenyl)disiloxane [17]. When the reaction mixture was diluted, dodecaphenyldodecasilsesquioxane (phenyl-T 12 ) was obtained in 95% yield, while an increase in the concentration of the starting compound led to PPhSSO [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The 29 Si NMR spectroscopy method demonstrated that the reaction of hydrolysis–condensation of phenyltrimethoxysilane in the presence of a basic catalyst in different conditions occurred through an intermediate, tetrahydroxy(diphenyl)disiloxane [17]. When the reaction mixture was diluted, dodecaphenyldodecasilsesquioxane (phenyl-T 12 ) was obtained in 95% yield, while an increase in the concentration of the starting compound led to PPhSSO [17,18]. Hydrolysis of HSi(OMe) 3 in an acidic medium gave rise to tetramethoxydisiloxane as an intermediate compound, the thermal polycondensation of which afforded ladder organosilsesquioxane [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the strategies of Albert, the existence of a T 1 species has been proved as the principal intermediate products in the synthesis of T 12 ‐phenyl compound . Studies of Kim and David on the synthesis of T 8 ‐phenyl compound have confirmed that the reaction pathway for T 8 ‐phenyl compound may occur through the condensation of the two tetraol T 2 species (Scheme ) .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In order to improve upon the compatibility issues with inorganic materials, inorganic-organic hybrid materials such as silsesquioxanes have been touted as appropriate material due to both organic functional group and inorganic siloxane networks providing a bridge between both phases enabling high compatibility between organic polymer networks. While cage structured polyhedral oligomeric silsesquioxanes, commonly known as polyhedral oligomeric silsesquioxane (POSS) [18][19][20], have been widely reported as polyimide hybridization material [21], their low molecular weight, as well as relatively low solubility in organic solvents have limited their effectiveness as filler in many cases [22].…”
Section: Introductionmentioning
confidence: 99%